Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Matematika Berbasis HOTS Materi Pola Bilangan Berdasarkan Kriteria Hadar - Halim, St. Nur Humairah; Tahir, Sitti Rahmah; Syahri, Andi Alim; Husriana, Husriana (FKIP Universitas Mataram, 2021)
This study aims to determine the types of errors made by class VIII students of SMP Satap 3 Tellu Limpoe, Bone Regency, in solving mathematics problems based on Higher Order Thinking Skills on number pattern material based on Hadar criteria. The subjects in this study were class VIII SMP Satap 3 Tellu Limpoe, Bone Regency, which amounted to 14 people, then 2 students were selected as research subjects to be interviewed, namely students who made the most mistakes based on the Hadar error criteria indicator. The research instrument was used in the form of a HOTS-based math test for number patterns and interview guidelines. While the data were analyzed using qualitative descriptive analysis and continued with triangulation techniques to test the validity of the data. The results obtained are the types of errors made by class VIII students of SMP Satap 3 Tellu Limpoe, Bone Regency in solving mathematics problems based on Higher Order Thinking Skills on number pattern material based on Hadar criteria, including (1) errors in using data, (2) errors in interpreting language, (3) errors using logic when concluding, (4) errors using definitions or theorems, and (5) the solution is not checked again.